2021
DOI: 10.1111/jgs.17558
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of self‐ and proxy‐rated hearing among older adults with and without cognitive impairment

Abstract: Background: Hearing loss is highly prevalent among older adults with cognitive impairment and may exacerbate neuropsychiatric symptoms and affect interactions with others. Although audiometry is the gold standard for measuring hearing, it is not always used in research or clinical settings focused on the care of individuals with cognitive impairment. Subjective assessments of hearing, both self-and proxyrated, are widespread but may not adequately capture the presence of hearing loss as compared to audiometry.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…The NACC‐UDS data rely on a binary yes/no approach to self‐reported HL. Research comparing audiometric data with self‐report has shown that with greater levels of cognitive impairment, HL may go under‐reported and unaddressed (i.e., the sensitivity of self‐rated hearing dropped from 71% for CN adults to 61% for adults with MCI to 53% for persons with dementia) 48 . Hearing aid use could be a surrogate for socioeconomic factors, financial resources, access to healthcare, the ability and willingness to use amplification and availability of social support—variables not collected in the UDS.…”
Section: Discussionmentioning
confidence: 99%
“…The NACC‐UDS data rely on a binary yes/no approach to self‐reported HL. Research comparing audiometric data with self‐report has shown that with greater levels of cognitive impairment, HL may go under‐reported and unaddressed (i.e., the sensitivity of self‐rated hearing dropped from 71% for CN adults to 61% for adults with MCI to 53% for persons with dementia) 48 . Hearing aid use could be a surrogate for socioeconomic factors, financial resources, access to healthcare, the ability and willingness to use amplification and availability of social support—variables not collected in the UDS.…”
Section: Discussionmentioning
confidence: 99%
“…Again, the authors' new contribution is this apparent trend: greater cognitive impairment is associated with lower sensitivity and specificity of self‐report using audiometry as the gold standard. It is therefore important to appreciate the overlap in confidence intervals for many of the estimates of sensitivity and specificity defined by cognitive classification groups in Kim et al's Table 2 5 . The authors do not provide formal statistical tests of between‐group differences.…”
Section: Figurementioning
confidence: 99%
“…One approach would be to screen by asking about hearing problems and refer those with self‐reported difficulty to an audiologist. But a report published in this issue of the Journal by Kim et al casts doubt on this practice 5 . Using data collected as part of the Atherosclerosis Risk in Communities Neurocognitive Study (ARIS‐NCS), the authors found low concordance between self‐reported hearing problems and objective hearing loss, as measured by audiometric pure‐tone averages.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…She cautioned that hearing (and listening) problems may (and often do) parade as cognitive problems and vice versa, thus potentially leading to an incorrect diagnosis and inappropriate (or no) treatment. Kim, Betz, Albert et al 8 report subjective self and proxy-reports of hearing loss are widespread but often do not accurately characterize the actual severity or degree of hearing loss for adults with and without cognitive decline. The authors report 3,326 self-rated and 520 proxyrated hearing assessments.…”
Section: Beckmentioning
confidence: 99%